Usefulness for the combination of G protein- and β-arrestin-biased ligands of μ-opioid receptors: Prevention of antinociceptive tolerance. Issue 1 (November 2017) - Mori, Tomohisa; Kuzumaki, Naoko; Arima, Takamichi; Narita, Michiko; Tateishi, Ryunosuke; Kondo, Takashige; Hamada, Yusuke; Kuwata, Hirotsugu; Kawata, Miho; Yamazaki, Mitsuaki; Sugita, Kazuyuki; Matsuzawa, Akinobu; et al.
Background: µ-Opioid receptor internalization is considered to be critically linked to antinociceptive tolerance. Although µ-opioid receptor agonists have been administered simultaneously with other drugs to control pain, little information is available regarding opioid–opioid interactions. Therefore, the present study was designed to further investigate the utility of a new G protein-biased ligand for µ-opioid receptors, TRV130, which has an antinociceptive effect without β-arrestin-dependent µ-opioid receptor internalization, and its combination with fentanyl using µ-opioid receptor-expressing cells and mice. Results: In the present study, we confirmed that fentanyl produced a profound increase in β-arrestin-2 recruitment accompanied by µ-opioid receptor internalization, whereas TRV130 did not induce either the recruitment of β-arrestin-2 or µ-opioid receptor internalization in µ-opioid receptor-expressing cells. Under these conditions, β-arrestin-2 recruitment accompanied by µ-opioid receptor internalization induced by fentanyl was abolished by TRV130, whereas TRV130 did not alter the reduction of cyclic adenosine monophosphate formation by fentanyl in µ-opioid receptor-expressing cells. In a behavioral assay, TRV130 exerted an antinociceptive effect in a hot-plate test in mice. In a combination test, the antinociceptive effect of TRV130 was synergistically increased by fentanyl. Fentanyl induced antihyperalgesia and development of its tolerance under a neuropathic pain-like state following sciatic nerve ligation. However, treatment of mice with an antinociceptive dose of TRV130 did not induce the rapid development of tolerance to its antihyperalgesic effect under a neuropathic pain-like state. Furthermore, the rapid development of tolerance to the antihyperalgesic effect induced by fentanyl plus TRV130 in mice with sciatic nerve ligation was not observed, unlike in the case of fentanyl alone. Conclusions: These findings provide evidence that activation of the G protein-biased pathway through µ-opioid receptors can alter signaling in the β-arrestin-2 pathway linked to the stimulation of µ-opioid receptors. Furthermore, the combination of G protein-biased and β-arrestin-biased ligands of µ-opioid receptors exerts an ideal antinociceptive effect without the rapid development of antinociceptive tolerance.